Trance Phenomenon “Kesurupan’’ in the Tarawangsa Art of Rancakalong Sumedang - Firman Adi Saputra; Samsul Rizal; Anggha N. Sefurridjal; Aris Ardiansyah; Muhamad Ilyas (Pascasarjana ISBI Bandung Conference Series, 2025)
This article explores the phenomenon of trance known as "kesurupan" in the traditional art of Tarawangsa in Rancakalong, Sumedang. Tarawangsa, originating from the agrarian community of Sumedang, is a unique cultural expression deeply rooted in local traditions. The study delves into the etymology, historical context, and other essential components of Tarawangsa performances in Rancakalong, Sumedang. Specifically, the article focuses on the occurrence of trance states during the Nyumpingkeun phase and examines the relationship between entrainment, biomusic phenomena, and the trance experienced by participants in this art form. Keywords: Entrainment; Tarawangsa Art; Ritual Ceremonies; Kesurupan; Biomusic